Equivalence in the Particular Theory of Translation in the Example of English and Russian Languages - Ilkhomova Mohina (Research Parks Publishers, 2023)
This article addresses general linguistic issues related to the theory and practice of translation. During the translation process, the translator has to solve many linguistic issues related to phonetics, stylistics and grammar of the source language and the target language, about the features of the functional style to which the original belongs, with the problem of transferring content and the problem of achieving equivalence. The pa6ote reveals the concept of equivalence in translation theory, examines problems of translation semantics, and draws typological differences in the systems of English and Russian languages. The topic of work is relevant due to the fact that cross-linguistic issues are located in the area of intercultural communication. It is necessary not only to have knowledge in a certain subject area, but also to understand the differences in language systems in order to convey the informational part of the original with the least amount of effort.